Molecular systematics, mating population and mycotoxin production of Fusarium graminearum from grasses. - Zakaria, Latiffah (Universiti Sains Malaysia, 2015)
Fusarium is one of the heterogeneous genera of saprophytic, pathogenic, and toxigenic fungi distributed worldwide. Several Fusarium species normally found in the temperate and subtropical regions were also reported to be in the highlands of tropical areas, including Malaysia. This research was to identify Fusarium species in context of occurrence, diversity, and toxigenicity. Sampling was done randomly from variable hosts and substrates in Cameron Highlands, Fraser's Hill and Kinabalu Park.